IDENTIFIKASI MATERI LOKAL SEBAGAI SUMBER BELAJAR SAINS BIOLOGI SMP DI KOTA PALEMBANG - Heni Indri Yastuti; Meilinda Meilinda; Khoiron Nazip (Jurnal Pembelajaran Biologi: Kajian Biologi dan Pembelajarannya, 2014)
Abstrac: This study aimed to obtain information about local materials on Palembang covering local wisdom, local potential and local environmental problems that qualify as learning resources of biology science for junior high school. The experiment was conducted in Palembang with sample location includes Kecamatan Bukit Kecil, Ilir Barat I, Gandus, Sukarami, Kalidoni, Seberang Ulu I, Seberang Ulu II dan Kertapati, runs from February to May 2014 method used is descriptive and information regarding the material locally obtained through observation, in-depth interviews and related literature. The results showed that there are many local materials on Palembang is qualified as biology learning resource for junior high school consisting of local wisdom, local potential, and local environmental problems. On local wisdom include myths around the garden tombs Bukit Siguntang towards the preservation of ecosystems and habits of the people living in Rumah Panggung. At the local potential include the Musi River ecosystem; natural park ecosystems Punti Kayu; utilization of Kambang Iwak Besar as a place of sports; waste into a product that does not damage the environment; cultivation of fish in fish breeding centers; interaction pattern formed on the fields; cultivation butterflies in the butterfly garden; and diversity of living things in the area Agropolitan. On local environmental problems include changes in water quality from the disposal of liquid dye songket; silting up of rivers due to sand mining; water hyacinth population explosion as a result of fish farming cages; over the land of swamps to residential areas; and the impact of air pollution from vehicle fumes, factory smoke fertilizers, as well as a rubber factory smoke. The results of this study can be used as a reference for teachers in implementing the science learning biology for junir high school and in the development of teaching materials sourced locally on the material in Palembang. Â